PENGARUH KUALITAS PELAYANAN, PERCEIVED VALUE SERTA CORPORATE IMAGE TERHADAP KEPUASAN PELANGGAN BANDAR UDARA - Wandik, Kandius; Abadi, Ferryal (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The purpose of this study was to see how much about the effect of service quality, Corporate Image and Perceived Value on customer satisfaction at Sentani-Jayapura International Airport. In this study, Corporate Image is a moderating variable in the effect of service quality and Perceived Value on customer satisfaction at Sentani-Jayapura International Airport. This research uses a quantitative approach using SEM-PLS analysis. The research results show that there are Service quality has a positive effect on Corporate Image, Perceived Value has a positive effect on Corporate Image, Service quality has a positive effect on Customer Satisfaction, Perceived Value has a positive effect on Customer Satisfaction, Corporate Image has a positive effect on Customer Satisfaction, and Service Quality has a positive effect on Customer Satisfaction through Corporate Image, Perceived Value has a positive effect on Customer Satisfaction through Corporate Image